2018
DOI: 10.1111/ppc.12336
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone addiction in Tibetan and Han Chinese adolescents

Abstract: Purpose To compare mobile phone addiction (MPA) patterns between Tibetan and Han adolescents in China. Design and Methods The study was carried out in two provinces of China. The Mobile Phone Addiction Scale (MPAS) was used to assess MPA. Findings Seven hundred and five Tibetan and 606 Han students participated in the study. The MPAS total score was 24.4 ± 11.4 in the whole sample; 27.3 ± 10.8 and 20.9 ± 11.2 in Tibetan and Han students, respectively. Quality of life (QOL) in the physical, psychological, socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Third, the instruments were self-reported screening tools and not diagnostic tools. There has been no agreement on the definition and diagnostic criteria of mobile phone addiction, therefore, following other studies (Chiu, Hong & Chiu, 2013;Hong et al, 2019;Lu et al, 2019), only a self-reported scale on the severity of mobile phone addiction could be employed.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the instruments were self-reported screening tools and not diagnostic tools. There has been no agreement on the definition and diagnostic criteria of mobile phone addiction, therefore, following other studies (Chiu, Hong & Chiu, 2013;Hong et al, 2019;Lu et al, 2019), only a self-reported scale on the severity of mobile phone addiction could be employed.…”
Section: Discussionmentioning
confidence: 99%
“…4 Further studies show that the rate of IA increases as the duration of Internet use increases. 23,25,27,28 Gök 25 and Mohammed 23 both reported that the technology addiction rate was higher in those who use technology more than 3 hours and 12 hours (compared with those who use it 4-8 hours), respectively, than those who spend less time using technology. Another study concluded that gaming addiction increases with an increased duration of playing games.…”
Section: Discussionmentioning
confidence: 99%
“…25,29,[31][32][33] This study further showed that there is a positive correlation between low academic achievement and IA and DGA, as supported by similar results in several studies. 27,30,[34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, the prevalence of smartphone addiction risk among children aged less than 10 rose from 17.9% in 2016 to 20.7% in 2018, which was the largest increase in any of the age groups [4]. Problematic smartphone use typically involves not the telephone but rather the device's internet capability [15][16][17][18][19][20][21][22][23], which is an application capability designed for a particular purpose [24]. Problematic use of the applications for entertainment (gaming being one of its forms), instant messengers and social networking services (SNS) can be generally more likely to contribute to smartphone addiction [18,19,[21][22][23]25].…”
Section: Introductionmentioning
confidence: 99%
“…Problematic use of the applications for entertainment (gaming being one of its forms), instant messengers and social networking services (SNS) can be generally more likely to contribute to smartphone addiction [18,19,[21][22][23]25]. Smartphone addiction can negatively affect self-esteem, physical and mental health, and social relationships, especially among children or adolescents [12,15,[25][26][27]. Its impact on younger children is expected to be more severe.…”
Section: Introductionmentioning
confidence: 99%